Intercountry Comparisons of Labor Force Trends and of Related Developments: An Overview - Mincer, Jacob (Journal of Labor Economics, 1985)
This paper is a survey of analyses of women's labor force growth in 12 industrialized countries, originally presented at a conference in Sussex, England, in June 1983. The main focus of the conference papers and of the current survey is on growth of the labor force of married women in the years 1960-80. Trends in fertility, wages, and family instability also receive attention as related developments. Married women's labor force growth is observed in all countries, except for the USSR after 1970, where labor force rates of women reached the level of men. Growth rates differ among countries. They apparently respond to growth in real wages and to growth in education, but response elasticities differ among countries. Estimates of these elasticities contained in the country papers were helpful in predicting the trends. Other findings include ubiquitous declines in fertility and growth of divorce in the 1970s. Both developments are related to long-run labor force growth. In all countries, wages of women were lower than wages of men. The 1960 average gap of 38% narrowed to 29% in 1980. Factors related to these trends, including public policy, are discussed in the survey.